Sex differences in hydration status among adolescent elite soccer players - Francescato, M. P.; Venuto, I.; Stella, A. B.; Stel, G.; Mallardi, F.; Cauci, S. (Journal of Human Sport & Exercise, 2019)
Hydration of athletes may affect performance and health status likely with differences among sexes. We studied the impact of sex on hydration behaviour in adolescent athletes. Hydration status and urine markers were investigated in 7 female and 7 male elite 16 years-old soccer players in temperate climate (21-24°C). Participants consumed water ad libitum during the first training session (LIB), whereas in the second session (HYD) they drunk a water amount matching 70% of sweat loss from the LIB session. Post-training performances were evaluated by Yo-Yo intermittent recovery level 1 (IR1) test and countermovement jump (CMJ). Body mass values were recorded and urine samples were collected before and after each experimental session. Males drunk a double amount of water in HYD (1.19±0.21 kg) compared to LIB (0.62±0.19 kg; p=0.001; ES=2.88), resulting in a lower percentage body mass loss (HYD -0.95±0.63% versus LIB -1.59±0.33%; p=0.044; ES=-1.35); total distance of Yo-Yo IR1 was higher, albeit not significantly, in HYD (2953±779 m) than in LIB (2103±939 m); CMJ performance was unchanged. In females, water drunk, body mass, Yo-Yo IR1 and CMJ did not vary in HYD versus LIB sessions. In adolescent males a 70% sweat replacement personalized hydration regimen reduced body mass loss and tended to improve performance, whereas in females ad libitum water drinking allowed to maintain hydration status (<1% body mass loss). Our results suggest that coaches and athletes themselves should consider a personalized hydration regimen for adolescent male soccer players, whereas ad libitum drinking seems suitable for females.